Synthesis Conditions of Mesoporous NaA Zeolites - Meng, Ying; Li, Fu-Xiang; Feng, Yan-Chao; Xue, Jian-Wei; Lv, Zhi-Ping (Asian Journal of Chemistry, 2013)
Mesoporous NaA zeolites were successfully synthesized by a direct hydrothermal method using tetraethylorthosilicate and [3-(trimethoxysilyl)propyl]octadecyl-dimethyl ammonium chloride (TPOAC) as the silicon source and mesopore-generating agent, respectively. The effects of the synthesis conditions, including the added amount of [3-(trimethoxysilyl)propyl]octadecyl-dimethyl ammonium chloride, crystallization temperature and gel alkalinity, were investigated. The as-synthesized materials were characterized by X-ray diffraction, nitrogen adsorption-desorption measurements, scanning electron microscopy and transmission electron microscopy. The sample mesopore walls were found to be comprized of NaA zeolite frameworks. The sample size and mesopore structure were affected by the added amount of [3-(trimethoxysilyl)propyl]octadecyl-dimethyl ammonium chloride. The crystal phase was affected by the crystallization temperature and gel alkalinity.